2011
DOI: 10.3109/0284186x.2011.633556
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with concordant estrogen receptor expression at diagnosis and centralized re-assay in a Danish population-based breast cancer study

Abstract: Background Estrogen receptor (ER) expression predicts tamoxifen response, which halves the risk of breast cancer recurrence. We examined clinical factors associated with concordance between ER expression at diagnosis and centralized re-assay, and the association of concordance with breast cancer recurrence. Materials and Methods We used immunohistochemistry to assess ER expression on archived fixed, paraffin-embedded breast carcinoma tissue excised from women aged 35–69 years, diagnosed 1985–2001 in Jutland,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The blocks derived from patients with centrally confirmed [94] ER+ stage II breast cancer diagnosed in 2000 or 2001. From each block, three 10-micron sections were cut to slides, the first of which was hematoxylin and eosin (H&E) stained to identify regions of highest tumor cellularity, which were then demarcated on the unstained slides.…”
Section: Methodsmentioning
confidence: 99%
“…The blocks derived from patients with centrally confirmed [94] ER+ stage II breast cancer diagnosed in 2000 or 2001. From each block, three 10-micron sections were cut to slides, the first of which was hematoxylin and eosin (H&E) stained to identify regions of highest tumor cellularity, which were then demarcated on the unstained slides.…”
Section: Methodsmentioning
confidence: 99%
“…[39] A previous validation study using medical record review confirmed all recurrences, eliminating the potential for outcome misclassification, and showed perfect agreement for all covariates except one patient’s menopausal status. [40] Staining guidelines were designed to be clinically applicable to ensure that ApoD could be a practical predictive or prognostic indicator if an association was found.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, data were of high quality: the positive predictive value of the DBCG Registry’s recurrence classification was reported to be 99.4% (26), and this finding was confirmed by medical record review for a subset of cases in this study (15). Since our study covered a time period of evolving ER assay methodologies, we centrally re-assayed ER status for cases and controls using current standard clinical methods (27). Our use of TMAs allowed Pak1 and ERαS305-P to be assayed in one batch with single reagent lots, eliminating two major sources of staining variability common to immunohistochemical assays.…”
Section: Discussionmentioning
confidence: 99%